Factores que inciden en la transición de graduados de la carrera de Ingeniería Comercial de la Universidad Técnica de Cotopaxi al mercado laboral. - Ayala Quisaguano, Sandy Gabriela (2020)
The present research intends to estimate that influence transition factors of students at Commercial Engineering career of Technical University of Cotopaxi to the labor market through Cox semi - parametric model application. Starting data correspond to graduates from April 2016 period to April 2018 period accessing to personal, family, work and economic information. In the investigation a quantitative methodology is applied with descriptive and deductive approach, a statistical analysis is carried out through the semi-parametric Cox method in two forms: in the first one the covariates associated with survival were included individually and in the second the effects of covariates associated with cross-survival were included. Having as result that the main factors that affect this problem is work experience that the person obtains through the study process and the proximity between the University and the place where is found their first significant job.